Efektifitas Program Perluasan Dan Penempatan Tenaga Kerja Terhadap Penurunan Angka Pengangguran Di Kepulauan Riau - Rachel Damayanti Gultom; Karmi Octaviani; Sri Wahyuni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The research purposes to determine effectiveness of the Manpower Expansion and Placement Program towards reducing the unemployment rate in the Riau Islands. This research is qualitative research with a descriptive approach. Data collection techniques are carried out by literature and documentation studies which are collecting data from records, administration, documents, books, and scientific works. Data analysis techniques were by reducing data, presenting data, and drawing conclusions. The results of the study are seen from the achievement of effectiveness indicators, namely a good understanding of the program because there is community participation and collaboration with various parties, target accuracy are running well because there is absorption of job vacancies, the timeliness of the program for a year, the achievement of goals by decreasing the unemployment rate even though it is not too much, and real changes in the impact of job training so that people have jobs and are placed according to their experience.